Jom Masuk U Opportunities for students to choose IHLs for career prospects - Mimi Rabita, Abdul Wahit (2023)
JOHOR BAHRU, 21 May, 2023 - The coordination of the ‘Jom Masuk U’ (JMU) program held at six locations according to zones serves as a centralized hub to obtain various information for pursuing studies at the highest level.